A Rare Case of Invasive Neisseria meningitidis Presenting with Severe Stridor and Negative CSF Findings - Mostafa Eisa , Reda Sherif , Mohamed H. Badawy , Mohamed Javid, Engy Abdallah , Anas Hamadelneil , Khaled Aldebese (South Eastern European Journal of Public Health, 2025)
Background: Neisseria meningitidis is a gram-negative diplococcus that causes bacterial meningitis and sepsis. However, invasive meningococcal disease (IMD) can present in unexpected ways, making early identification and treatment challenging. We report a rare case of invasive N. meningitidis infection with significant upper airway obstruction and negative cerebrospinal fluid (CSF) findings. Case Presentation: A 55-year-old man with a history of type 2 diabetes mellitus arrived with severe respiratory distress, high temperature, and increasing stridors. The first examination indicated tachypnea, inspiratory stridor, and oropharyngeal erythema without meningismus. Despite the suspicion of bacterial meningitis, CSF examination revealed no pleocytosis or recognizable pathogens on Gram stain and culture. However, blood cultures revealed N. meningitidis, indicating an invasive infection. The condition quickly worsened, necessitating intubation and critical care assistance. Empirical intravenous ceftriaxone and corticosteroids were administered, resulting in clinical improvement. The patient was successfully extubated after 7 days and released with no neurological complications. Conclusion: This case underscores an unusual presentation of invasive N. meningitidis with airway compromise and negative CSF findings. Clinicians should maintain a high index of suspicion for atypical Invasive meningococcal disease presentations to facilitate early diagnosis and treatment